Common-mode voltage mitigation of dual three-phase voltage source inverters in a motor drive application - Alcaide, Abraham Marquez; Wang, Xuchen; Yan, Hao; Leon, Jose I.; Monopoli, Vito Giuseppe; Buticchi, Giampaolo; Vazquez, Sergio; Liserre, Marco; Franquelo, Leopoldo G. (Institute of Electrical and Electronics Engineers Inc., 2021)
Electric variable speed drives (VSDs) based on two VSDs connected to a multiphase machine are an attractive solution to replace high-power mechanic and hydraulic systems in many sectors of industry and transportation because they present high performance with reduced cost, volume and weight. Among the causes which affect the reliability of dual VSDs, the common-mode current flowing through the machine bearing is an important issue. This paper faces the mitigation of the common-mode current by reducing the common-mode voltage (CMV) generated by the operation of a dual VSD. The CMV reduction is carried out without introducing any extra device and/or passive filtering method. This CMV reduction is performed by applying a specific phase-displacement between the modulation strategies of each single inverter drive. The proposed technique has been evaluated in a down scaled experimental setup in order to test its effectiveness